Impacts of child sponsorship communications: findings from World Vision programmes. Issue 3 (3rd April 2023) - Feeny, Simon; Clarke, Matthew; Westhorp, Gill; Jennings, Michael; Donohue, Cara
ABSTRACT: Child sponsorship programmes often seek to establish a personal relationship between a sponsor and child through the exchange of letters, photos, and sometimes gifts. This paper examines the impact of these activities using data from communities supported by World Vision in Georgia, Ethiopia, Peru, Senegal, and Sri Lanka. Findings indicate that some types of communications were associated with higher levels of psychosocial wellbeing. While findings varied across country, survey data for sponsored and non-sponsored children provided evidence of jealously, although on average, it was weak. Findings from interviews indicated that some non-sponsored children and families experienced jealousy more intensely.